2016
DOI: 10.1039/c6sm01500j
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of the adsorbed layer at the substrate interface determines the glass transition of supported ultrathin polystyrene films

Abstract: To elucidate the mechanism underlying the effect of polymer/solid interfacial interactions on the dynamics of thin polymer films, the glass transition of thin end-functionalized polystyrene films supported on SiO-Si, such as proton-terminated PS (PS-H), α,ω-dicarboxy-terminated PS (PS-COOH), and α,ω-dihydroxyl-terminated PS (PS-OH), was investigated. All the PS films exhibited a substantial depression in T with decreasing film thickness, while the extent of such depression was strongly dependent on the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 75 publications
6
54
1
Order By: Relevance
“…Napolitano et al [11][12][13][14] demonstrated that substrate effects on the glass transition temperature (T g ) and segmental dynamics, measured in thin films upon confinement, could be directly related to the degree of chain adsorption at the substrate. Koga et al [15], Wang et al [16][17][18] revealed that suppressed dynamics of ultrathin adsorbed layers could extend tens of nanometers away from the substrate, which could be related to the thickness or architecture of the adsorbed layer.…”
Section: Main Textmentioning
confidence: 99%
“…Napolitano et al [11][12][13][14] demonstrated that substrate effects on the glass transition temperature (T g ) and segmental dynamics, measured in thin films upon confinement, could be directly related to the degree of chain adsorption at the substrate. Koga et al [15], Wang et al [16][17][18] revealed that suppressed dynamics of ultrathin adsorbed layers could extend tens of nanometers away from the substrate, which could be related to the thickness or architecture of the adsorbed layer.…”
Section: Main Textmentioning
confidence: 99%
“…1 The T g of ultrathin PS films could be adjusted by modifying the various aromatic groups anchored onto silicon substrate surfaces 3,5 and the loop size of the adsorbed polystyrene (PS) chains. 6,7 In other words, the local relaxation of the chains near the substrate appears to be suppressed by the various interactions between the substrate and polymer. Furthermore, the interfacial effect on the polymer properties is complex and the nature of the interfacial effect remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that entropic effects may also play a modifying role in understanding confinement effects. For example, changes in dynamics due to tethering and adsorption of chains to substrates have been reported, as well as variations for different chain architectures such as stars and cyclic chains that otherwise have identical chemical composition, suggesting that the presence of a boundary or interface alters the available entropic conformations and influences the local dynamics, altering the nature of the dynamical gradient. Recent studies have also reported unexpected MW dependences and chain stiffness effects to the glass transition temperature ( T g ) and surface dynamics that contradict the general understanding that had historically been formed.…”
Section: Introductionmentioning
confidence: 99%